Idiopathic Superior Mesenteric Vein Thrombosis Resulting in Small Bowel Ischemia in a Pregnant Woman - Hao Lin; Chih-Che Lin; Wan-Ting Huang (Case Reports in Obstetrics and Gynecology)
Background. Small bowel ischemia due to superior mesenteric vein thrombosis (MVT) is rare during pregnancy. However, additional precipitating factors should usually be identified. Case. A 31-year-old woman, pregnant at 34 weeks, was sent to the emergency department because of acute peritonitis. An emergency exploration revealed a segmental gangrene of the small intestine without any mechanical obstruction. Together with the termination of pregnancy, resection of the damaged small bowel was performed, and an end-to-end enterostomy was followed. Based on the operative and pathological findings, small bowel ischemia might be attributed to superior mesenteric vein thrombosis. Conclusion. Hypercoagulation state normally found in pregnant women is believed to lead to this catastrophic condition without other precipitating factors.